Pengaruh Variasi Arus Pengisian Pengosongan Muatan Pada Model Baterai Lead Acid Terhadap Perubahan Efisiensi Energi - Kurriawan Budi Pranata; Muhammad Priyono Tri Sulistyanto; Muhammad Ghufron; Mukhammad Yusmawanto (Lambung Mangkurat University Press, 2019)
This research aims to determine the energy efficiency of lead acid batteries after testing the charge-discharge process with a constant current method. Charge-discharge current variations of 0.3 A, 0.5 A, and 0.6 A. The performance voltage range when the charging process has a value in comparison with the charging current. The greater the charging electric current can change the voltage range of the greater performance. Conversely, at the discharge process. The greater the discharge electric current can change the performance voltage range the smaller. Meanwhile, in the performance voltage range the discharge process is lower if the discharge flow gets bigger. Based on the results of the charge-discharge process test, it can be determined the energy efficiency values of the current variation of 0.3 A, 0.5 A, and 0.6 A, which are 76.32%, 76.06% and 91.33%, respectively.